The Role of Social Media in Corporate Governance - Ang, James S.; Hsu, Charles; Tang, Di; Wu, Chaopeng (The Accounting Review, 2021)
ABSTRACT We examine whether social media criticisms posted by small investors can predict subsequent firm acquisition decisions. Specifically, we use textual analysis to examine the internet stock message board postings of 303 value-reducing acquisition attempts. Our empirical evidence shows that small investors' negative postings are able to predict a potential acquirer's subsequent decision to withdraw its attempt. We further find that this predictive ability increases with the information quality of postings, and that the predictive information extracted from social media is incremental to that captured by proposal announcement returns, conventional media coverage, analyst reports, and institutional investors' responses related to the proposed acquisition. Finally, we show that message board criticisms are also able to predict governance outcomes beyond acquisition decisions. Overall, our results are consistent with the notion that social media play a role in corporate governance by gathering crowd wisdom and uncovering additional value-relevant information. JEL Classifications: G34; G14; M41.